On vector lattices and rings of uniformly continuous functions - Aparina, L. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. В. Апарина. О векторных решетках и кольцах равномерно непрерывных функций L. Aparina. Apie tolygiai tolydinių funkcijų vektorines gardeles ir žiedus